XBP1 Modulates the Aging Cardiorenal System by Regulating Oxidative Stress - Ji Zhang; Yuanyuan Zhao; Nianqiao Gong (MDPI AG, 2023)
X-box binding protein 1 (XBP1) is a unique basic-region leucine zipper (bZIP) transcription factor. Over recent years, the powerful biological functions of XBP1 in oxidative stress have been gradually revealed. When the redox balance remains undisturbed, oxidative stress plays a role in physiological adaptations and signal transduction. However, during the aging process, increased cellular senescence and reduced levels of endogenous antioxidants cause an oxidative imbalance in the cardiorenal system. Recent studies from our laboratory and others have indicated that these age-related cardiorenal diseases caused by oxidative stress are guided and controlled by a versatile network composed of diversified XBP1 pathways. In this review, we describe the mechanisms that link XBP1 and oxidative stress in a range of cardiorenal disorders, including mitochondrial instability, inflammation, and alterations in neurohumoral drive. Furthermore, we propose that differing degrees of XBP1 activation may cause beneficial or harmful effects in the cardiorenal system. Gaining a comprehensive understanding of how XBP1 exerts influence on the aging cardiorenal system by regulating oxidative stress will enhance our ability to provide new directions and strategies for cardiovascular and renal safety outcomes.